Detecção de genes diferencialmente expressos em Melipona Scutellaris (Hymenoptera, Apidae) - Santana, Flávia Assumpção (2003)
Bees have the most varied degrees of sociability, from solitary to eusocial species. In the colonies of eusocial bees there are two queen and worker castes, and males, each with specific functions. KERR proposed a model of gene regulation to explain 3: 1 segregation at birth in Melipona larvae, whereby two major genes Xa and Xb, with two alleles each, were responsible for feminizing products. Juvenile Hormone (HJ) is one of the most important insect hormones, influencing the main functions of its complex physiological system. In this study, we used the Differential Display Reverse Transcriptase-Polymerase Chain Reaction (DDRT-PCR) technique to compare the gene expression of Melipona scutellaris in worker and adult queen, natural and juvenile hormone-induced queen and post embryonic ontogenetic development. Differentially expressed fragments were obtained with primer combinations: HT11G-AP05; HT11C-AP05; HT11G-OPF12; HT11G-OPA16. The HT11G-AP05 combination revealed in L1 (larva 1) and L2 (Iarva2, a cloned, sequenced and analyzed product in a database, showed identity with a protein domain of Clostridium sporogenes thiorredoxin disulfide reductase, an important protein in In L1 and L2 the combination of the HT11G-OPA16 primers revealed a product that showed identity with the Drosophila salH gene, a gene that codes for a protein required for the formation of antero-posterior structures during embryogenesis and whose product If the identity of these two genes, thioredoxin and sallt, is confirmed, it would be possible to infer similar and relevant functions in embryonic development and regulation of genes near heterochromatic regions for Melipona. maintenance of its highly heterochromatic state in Melipona.